2017
DOI: 10.1002/14651858.cd010470.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for managing taste disturbances

Abstract: Analysis 1.3. Comparison 1 Zinc versus placebo, Outcome 3 Taste acuity improvement for different taste sensations. Analysis 1.4. Comparison 1 Zinc versus placebo, Outcome 4 Taste acuity improvement-Cross-over study.. .. . Analysis 1.5. Comparison 1 Zinc versus placebo, Outcome 5 Taste acuity improvement-Objective outcome-Dichotomous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 82 publications
0
28
0
Order By: Relevance
“…12 A decrease in salivary gustin causes taste and smell disorders. 13 Zinc also increases salivary calcium concentration 14 which allows taste buds to work properly. 15 Finally, zinc is a co-factor of alkaline phosphatase, a significant enzyme in the membrane of taste buds.…”
Section: The Anatomy and Physiology Of Tastementioning
confidence: 99%
See 1 more Smart Citation
“…12 A decrease in salivary gustin causes taste and smell disorders. 13 Zinc also increases salivary calcium concentration 14 which allows taste buds to work properly. 15 Finally, zinc is a co-factor of alkaline phosphatase, a significant enzyme in the membrane of taste buds.…”
Section: The Anatomy and Physiology Of Tastementioning
confidence: 99%
“…The authors of the Cochrane review of these studies concluded that, overall, there was ''limited evidence'' on the primary outcomes of taste acuity and discrimination and ''is not conclusive in demonstrating improvement in taste perception.'' 14 Empirical Treatment: Is There a Pathophysiological Basis for Efficacy?…”
Section: The Zinc Studiesmentioning
confidence: 99%
“…It has been postulated that zinc supplementation may restore taste sensation in patients with both idiopathic and zinc deficiency-associated taste disturbances. Although the results of clinical trials have been inconsistent, a comprehensive Cochrane meta-analysis reveals some evidence to support the use of zinc supplementation to treat taste disturbances as measured by objective descriptors of taste acuity, particularly in zinc-deficient cohorts [3,[19][20]. Our zinc-deficient patient's chronic hypogeusia improved rapidly with zinc supplementation.…”
Section: Discussionmentioning
confidence: 92%
“…Total dysgeusia is defined as the inability to interpret all basic tastes which, in most cases, is associated with mineral deficiency (1). This condition can cause a loss of appetite and even malnutrition (2).…”
Section: Introductionmentioning
confidence: 99%
“…The inflammation caused by radiotherapy, smoking habit, zinc deficiency, drugs use, medications, chlorhexidine mouthrinse, xerostomia and nerve damage (chorda tympani or glossopharyngeal) can also cause dysgeusia (2,3). In addition, brain tumors, as well as psychiatric, depression and anxiety symptoms, can be associated with alterations in taste (4).…”
Section: Introductionmentioning
confidence: 99%